Kinetics Study of Acid Catalyzed Degradation of Glucose in High-Temperature Liquid Water - Atiqa Rahmawati; Aulia Iin Saputri; Ignatius Gunardi (University of Muhammadiyah Malang, 2020)
Glucose is the most abundant monosaccharide in nature, glucose obtained from cellulose and starch, it is many used to degradation process, and for the production of several organic compounds, one of the degradation products of glucose is an HMF (5-hydroxymethylfurfural). HMF is a platform chemical, which can be converted into several chemical and liquid fuels through hydrogenation, oxidation, and esterification. The objective of this researches has studied the kinetics of glucose degradation using acid-catalyzed (H2SO4) in high-temperature liquid water and observe the effect of acid concentration and temperature on degradation of glucose to HMF. In this research was used reactor with pressure 10 atm, with variation time of reaction, sulfuric acid concentration, and temperature of the reaction. From this research found kinetics of glucose degradation was followed by the first-order reaction in each variable. Activation Energy (Ea) values were 7306,593 J/mol; 6341,59 J/mol; 3988,14 J/mol and 3988,14 J/mol on the concentration sulfuric acid 0,05M; 0,1 M; 0,05M, from that result indicated that reaction rate was increase when activation energy was decrease this was related to Arrhenius equation. The effect of acid concentration on degradation glucose was the higher acid concentration used, the more glucose was degraded, and more HMF was formed. Meanwhile, the effect of temperature of reaction on degradation glucose was the higher temperature of the reaction, more glucose was degraded, and more HMF was formed. The highest value of HMF was in operation condition of concentration H2SO4 0,5 M at 175°C, with a time of reaction 120 minutes. However, the reduction rate of glucose was not equal to the rate of formation of HMF (5-hydroxymethylfurfural), it can be indicated that HMF (5-hydroxymethylfurfural) was not the only product of degradation of glucose, but the others product might be formed from this operating condition. The other product that might be formed was humin and levulinic acid.